Nutritional and Therapeutic Potential of Soursop - Muhammad Afzaal; Farhan Saeed; Aasma Asghar; Yasir Abbas Shah; Ali Ikram; Huda Ateeq; Muzzamal Hussain; Chigozie E. Ofoedu; James S. Chacha (Journal of Food Quality)
Soursop (Annona muricata) has been one of the most studied fruits in recent years, owing to its potential medicinal benefits, as evidenced by many studies. Soursop is a tropical and subtropical fruit having great versatility and is quite sensitive to drastic temperature fluctuations. Since soursop contains various phytochemicals, it can be used medicinally to treat a wide range of conditions, including diabetes (by inhibiting the enzymes α-glucosidase and α-amylase), tumor, cancer, oxidative stress, blood pressure, the induction of apoptosis in tumor cells as well as hemorrhagic disease and cholesterol lowering. Due to its significant nutritional profile and therapeutic potential, it can be utilized in the development of nutraceuticals and medicines. Its pulp, seed, and leaf extract are used as functional ingredients in different foods as value-added foods. This review article is intended to characterize fruit development patterns and examines potential maturity indicators in soursop. In addition, it also elaborates on the potential nutritional and active phytochemicals present in this magnificent gift of nature and their possible uses in the food and pharmaceutical industries.